2012
DOI: 10.3357/asem.3129.2012
|View full text |Cite
|
Sign up to set email alerts
|

Modafinil as a Replacement for Dextroamphetamine for Sustaining Alertness in Military Helicopter Pilots

Abstract: Like previous research, this study strongly suggests that both drugs can maintain acceptable levels of mood and performance during sleep deprivation. The results also confirm that modafinil is well tolerated and appears to be a good alternative to dextroamphetamine for countering the debilitating mood and cognitive effects of sleep loss during sustained operations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(36 citation statements)
references
References 20 publications
0
36
0
Order By: Relevance
“…In contrast, in a more recent study, Dackis et al (2012) showed that modafinil failed to decrease the positive urine samples for cocaine in drug addicts. Another concern regarding the clinical relevance of our study is the increasing use of modafinil for non-medical purposes, such as to increase cognitive ability (Cakic, 2009), to sustain alertness in military pilots (Estrada et al, 2012) and even to improve performance in athletes (Strano Rossi and Botrè, 2011). Of note, recent studies have demonstrated that modafinil produces a number of serious side effects, such as psychotic symptoms (Wu et al, 2008) and severe cutaneous (Stevens-Johnson Syndrome) and cardiovascular adverse reactions (Carstairs et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in a more recent study, Dackis et al (2012) showed that modafinil failed to decrease the positive urine samples for cocaine in drug addicts. Another concern regarding the clinical relevance of our study is the increasing use of modafinil for non-medical purposes, such as to increase cognitive ability (Cakic, 2009), to sustain alertness in military pilots (Estrada et al, 2012) and even to improve performance in athletes (Strano Rossi and Botrè, 2011). Of note, recent studies have demonstrated that modafinil produces a number of serious side effects, such as psychotic symptoms (Wu et al, 2008) and severe cutaneous (Stevens-Johnson Syndrome) and cardiovascular adverse reactions (Carstairs et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The relative efficacy of modafinil is further supported in a study conducted by the United States Air Force in comparing dextroamphetamine to modafinil in the ability of the respective drugs to counter the debilitating mood and Physiology & Behavior 142 (2015) 126-130 cognitive effects of sleep loss during long-term operations [5]. Both drugs were found to be effective in this regard.…”
Section: Introductionmentioning
confidence: 92%
“…Amphetamine, a wellknown psychostimulant, does not share a similar pharmacological profile when compared to modafinil [3]. Modafinil is different from dextroamphetamine (Adderall) in one major aspect; modafinil shows a low affinity for dopamine (DA) uptake binding sites [5].…”
Section: Introductionmentioning
confidence: 99%
“…Its strongest endorsement comes from the military [227] and astronautics [228]. In the United States military, modafinil has been approved for use on certain Air Force missions [229][230][231] as an adjunct to fight fatigue. It has been approved for use aboard the International Space Station where it helps with the disruptions in circadian rhythms and the reduced quality of sleep that astronauts experience [228].…”
Section: Nootropicsmentioning
confidence: 99%